Successful treatment of subinvolution of the placenta site with uterine artery embolisation, sparing the patient's fertility: A case report - Nour Saleh; Amin Bahabri; Ross Vander Wal (Case Reports in Women's Health)
Subinvolution of the placental site can lead to severe post-partum haemorrhage, though it is a rare cause of the condition. Subinvolution of the placental site is an abnormal persistence of widely dilated uteroplacental spiral arteries in the absence of retained products of conception, and is associated with an increased risk of maternal morbidity and mortality. This report presents a case of an uneventful caesarean section that was followed by multiple presentations of major secondary post-partum haemorrhage, with a subsequent diagnosis of subinvolution of the placental site on histopathology. The patient was eventually treated with uterine artery embolisation after trials of medical and other interventional measures.